Superior mesenteric artery syndrome caused by weight loss in a malnourished Syrian man. (22nd January 2018) - Aljarad, Ziad; Mahli, Nihad; Nasser, Mahmoud; Alobied, Majd; Alkhaled, Mamdouh; Hamoud Alhussein, M Wafa; Alhamid, Ahmad; Mouakeh, Ahmad; Sankari Tarabishi, Ahmad
Abstract: Superior mesenteric artery syndrome is a rare cause of upper gastrointestinal obstruction in which the third part of the duodenum is compressed between the superior mesenteric artery and the abdominal aorta, and the compression of the duodenum is caused by a narrowed aortomesenteric angle. We report in this case a 35-year-old patient who came with features of small bowel obstruction, weight loss and had a history of malnutrition because of war. Multi-slice computerized tomography showed a narrowed aortomesenteric angle and distance. Conservative treatment was presented and, after 3 months of observation, the patient gained weight.